Edukasi Bahaya Judi Online dan Dampaknya Terhadap Kesehatan Mental Masyarakat di Kelurahan Pulokerto, Kecamatan Gandus, Kota Palembang: Education on the Dangers of Online Gambling and Its Impact on Community Mental Health in Pulokerto Subdistrict, Gandus District, Palembang City - Hapsari, Yuanita Dwi; Arianti, Yosi; Isyanawulan, Gita; Oktanedi, Aldri; Ilham, Ilal; Muslimah, Hayana; Aziz, Muhammad Fakhri (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
This activity was carried out as a preventive effort to raise public awareness of the social and psychological risks associated with online gambling practices. The phenomenon of online gambling in Palembang City has shown a significant increase, resulting in mental, economic, and social vulnerabilities within the community. The activity took place on Saturday, November 1, 2025, at the Pulokerto Village Mosque, involving 30 participants, including village officials, community leaders, PKK (Family Welfare Movement) cadres, youth, and parents. The method used was participatory socialization through interactive lectures, PowerPoint presentations, case studies, and reflective discussion sessions. The materials presented covered how online gambling operates, its impacts on mental health, and prevention strategies based on family and community engagement. The results of the activity indicated an increase in participants' understanding of the dangers of online gambling addiction and greater awareness of the importance of maintaining mental health amid digital advancement. This activity also encouraged a collective commitment among the community and village officials to reject online gambling practices and to develop follow-up programs focused on digital literacy education.